Carbon nanofiber-supported PdNi alloy nanoparticles as highly efficient bifunctional catalysts for hydrogen and oxygen evolution reactions. (20th August 2017) - Chen, Jiawei; Chen, Jiadong; Yu, Danni; Zhang, Ming; Zhu, Han; Du, Mingliang
Highlights: The PdNi/CNF catalyst was synthesized by facile electrospinning and carbonization processes. The PdNi/CNF mats were directly employed as highly efficient bifunctional catalysts for the HER and OER. The hybrid materials exhibited high catalytic activity and long-term stability during the HER and OER. We offer an effective and feasible method for generating hydrogen by water electrolysis. Abstract: Efficient bifunctional electrocatalysts for the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) must be developed to realize an inexpensive water-splitting system for large-scale applications. Herein, a novel PdNi carbon nanofiber (PdNi/CNF) catalyst was synthesized by facile electrospinning and carbonization processes. The size and homogeneity of the Pd−Ni alloy nanoparticles (NPs) could be effectively tuned by controlling the molar feed ratio of metal precursors .The morphology and structure of the PdNi/CNFs were characterized, and the working electrodes fabricated from the prepared catalyst mats were directly employed in the HER and OER. The PdNi/CNFs-1:2 catalyst exhibits high catalytic activity in the HER with a low overpotential of 55 mV at a current density of 10 mA cm −2 in an acidic solution. Moreover, under 1 M KOH electrolyte, an overpotential of 187 mV is required in the HER over the catalyst to arrive 10 mA cm −2 and an overpotential of 289 mV is achieved in the OER at the same current density. The superior HER and OER activities of the PdNi/CNFs are attributed to the synergistic effects of the PdNi alloy nanoparticles (NPs) assembled on the CNFs. This work provides a simple route for synthesizing highly efficient bifunctional electrocatalysts from 3d transition metals and a small amount of noble metals for hydrogen and oxygen evolution reactions.